THE IDEA OF LIBERALISM IN THE HISTORY OF SOCIOPOLITICAL THOUGHTS - Rakhmanov Abdimalik Ergashevich (European Journal of Humanities and Educational Advancements, 2024)
The article analyzes the emergence of the first buds of the idea of liberalism in the history of socio-political views, its enrichment and improvement in content at different stages of human history, and the emergence of its various forms. Also, in the current period of social development, the issues of democratization of society and development towards a highly civilized society were discussed on the basis of the new ideological rules of the doctrine of liberalism.